Carvedilol Exerts Neuroprotective Effect on Rat Model of Diabetic Neuropathy - Magadmi, Rania M.; Alsulaimani, Mujahid A.; Al-Rafiah, Aziza R.; Ahmad, Muhammad Saeed; Esmat, Ahmed (Frontiers in Pharmacology, 2021)
Diabetic neuropathy (DN) commonly occurs in diabetics, affecting approximately 50% of both type 1 and 2 diabetic patients. It is a leading cause of non-traumatic amputations. Oxidative stress could play a key role in the pathophysiology of DN. This study aimed to investigate the potential neuroprotective effect of carvedilol on STZ-induced DN in rats. Thirty male Sprague Dawley rats (weighing 200–250 g) were randomly divided into five groups (six/group), where group 1 (negative control) received only the vehicle (0.5% of carboxymethyl cellulose orally 1 mL/kg). DN was induced by a single injection of remaining rats with streptozotocin (STZ; 50 mg/kg, i.p.). After diabetes induction, group 2 served as the diabetic untreated animals; while groups 3 and 4 were treated with carvedilol (1 and 10 mg/kg/d, orally, respectively). Group 5 received α-lipoic acid as a reference neuroprotective (100 mg/kg/d, orally). All treatments were continued for 45 days after diabetes induction, followed by behavioural tests. After sacrificing the animals, dorsal root ganglia and sciatic nerves were collected for histopathological examination and biochemical assessments. Briefly, STZ administration caused cold allodynia, induced oxidative stress and increased nerve growth factor (NGF) concentration. Nevertheless, carvedilol improved the behavioural tests, ameliorated the oxidative imbalance as manifested by reducing malondialdehyde, restoring glutathione content and superoxide dismutase activity. Carvedilol also decreased NGF concentration in DRG homogenate. In conclusion, this study demonstrates the neuroprotective effect of carvedilol in an experimentally induced DN rat model through – at least partly - its antioxidant effect and reduced NGF concentration in DRG.